TINJAUAN LITERATUR TERHADAP PENERAPAN TEORI KEPEMIMPINAN DALAM ORGANISASI PENDIDIKAN - Lilia Ulya Amalia; Isna Juwita Sari (Journal of Practice Learning and Educational Development, 2025)
Leadership is a key factor in the effectiveness of educational organizations, as it influences the direction, culture, and quality of learning. Educational organizations play a role in shaping human resources through curriculum management, learning, academic quality assurance, and teacher development. This study aims to review the application of various leadership theories. This study uses a literature study method by reviewing various literature and previous research results. The results of the discussion show that each leadership theory has its own advantages and challenges in its implementation. Transformational leadership encourages innovation and motivation, while transactional leadership emphasizes efficiency. Instructional leadership focuses on improving the quality of learning, and servant leadership strengthens humanistic values. Educational leaders must be adaptive and able to choose a leadership model according to the needs of the institution in order to achieve optimal educational goals.